An e-marketplace of healthcare and social care services: the perceived interest - Cruz-Cunha, Maria Manuela (2013)
The health and social care sector is receiving growing attention for the last years, due to the increased life expectancy, the public demand for a better quality of life and for better health services. These requirements can be met with more cost-efficient approaches and using new technology-based solutions for providing services. The paper presents and discusses some of the main results of a study undertaken in Guimarães, a Municipality at the North of Portugal, on the perceived relevance of an e-Marketplace of social and healthcare services for the inhabitants in general, and in particular for people with special needs; the study also included the identification of the most relevant services to be offered by this platform and allowed concluding that such an e-Marketplace is of recognized relevance and that it is expected a good adhesion from the population.